Liposomes Affect Protein Release and Stability of ITA-Modified PLGA-PEG-PLGA Hydrogel Carriers for Controlled Drug Delivery - Kadlecová, Zuzana; Sevriugina, Veronika; Lysáková, Klára; Rychetský, Matěj; Chamradová, Ivana; Vojtová, Lucy (Biomacromolecules, 2024)
Fat grafting, a key regenerative medicine technique, often requires repeat procedures due to high-fat reabsorption and volume loss. Addressing this, a novel drug delivery system uniquely combines a thermosensitive, FDA-approved hydrogel (itaconic acid-modified PLGA-PEG-PLGA copolymer) with FGF2-STAB, a stable fibroblast growth factor 2 with a 21-day stability, far exceeding a few hours of wild-type FGF2's stability. Additionally, the growth factor was encapsulated in "green" liposomes prepared via the Mozafari method, ensuring pH protection. The system, characterized by first-order FGF2-STAB release, employs green chemistry for biocompatibility, bioactivity, and eco-friendliness. The liposomes, with diameters of 85.73 ± 3.85 nm and 68.6 ± 2.2% encapsulation efficiency, allowed controlled FGF2-STAB release from the hydrogel compared to the unencapsulated FGF2-STAB. Yet, the protein compromised the carrier's hydrolytic stability. Prior tests were conducted on model proteins human albumin (efficiency 80.8 ± 3.2%) and lysozyme (efficiency 81.0 ± 2.7%). This injectable thermosensitive system could advance reconstructive medicine and cosmetic procedures.
Keywords: nosiče léků; fibroblastový růstový faktor 2; Drug Carriers; liposomy; Liposomes; polyglactin 910; polyethylenglykoly; Humans; Fibroblast Growth Factor 2; lékové transportní systémy; Polyethylene Glycols; Drug Delivery Systems; Hydrogels; lidé; Polyglactin 910; hydrogely